Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s10578-013-0361-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prefrontal Oxygenation Related to Distractor-Resistant Working Memory in Children with Attention-Deficit/Hyperactivity Disorder (ADHD)

Abstract: This study aimed at investigating the effect of distraction on working memory and its underlying neural mechanisms in children with attention-deficit/hyperactivity disorder (ADHD). To this end, we studied hemodynamic activity in the prefrontal cortex using near-infrared spectroscopy while 16 children with ADHD and 10 typically developing (TD) children performed a working memory task. This task had two conditions: one involved a distraction during the memory delay interval, whereas the other had no systematic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 60 publications
0
28
0
1
Order By: Relevance
“…Most of the studies of children with ADHD show atypical patterns of oxyHb more prominently in the right hemisphere during a variety of tasks such as the reverse-Stroop task (Yasumura et al, 2014), executive attention control task (Tsujimoto et al, 2013), verbal fluency task (VFT; Schecklmann et al, 2009), Go/NoGo task (Monden et al, 2012, 2015; Xiao et al, 2012; Nagashima et al, 2014a), oddball task (Nagashima et al, 2014b,c), passive viewing of facial expression (Ichikawa et al, 2014), and emotional prosody recognition (Köchel et al, 2015). These studies have revealed hypoactivation in the right frontal lobe including the prefrontal cortex (PFC; Xiao et al, 2012; Yasumura et al, 2014), middle frontal gyrus (MFG), and inferior frontal gyrus (IFG) (Monden et al, 2012, 2015; Nagashima et al, 2014a,b,c), presumably because NIRS probes can easily be applied to the frontal region (see Table 1).…”
Section: Lateralization In Atypical Neural Function In Adhdmentioning
confidence: 99%
“…Most of the studies of children with ADHD show atypical patterns of oxyHb more prominently in the right hemisphere during a variety of tasks such as the reverse-Stroop task (Yasumura et al, 2014), executive attention control task (Tsujimoto et al, 2013), verbal fluency task (VFT; Schecklmann et al, 2009), Go/NoGo task (Monden et al, 2012, 2015; Xiao et al, 2012; Nagashima et al, 2014a), oddball task (Nagashima et al, 2014b,c), passive viewing of facial expression (Ichikawa et al, 2014), and emotional prosody recognition (Köchel et al, 2015). These studies have revealed hypoactivation in the right frontal lobe including the prefrontal cortex (PFC; Xiao et al, 2012; Yasumura et al, 2014), middle frontal gyrus (MFG), and inferior frontal gyrus (IFG) (Monden et al, 2012, 2015; Nagashima et al, 2014a,b,c), presumably because NIRS probes can easily be applied to the frontal region (see Table 1).…”
Section: Lateralization In Atypical Neural Function In Adhdmentioning
confidence: 99%
“…In another study, Tsujimoto et al (2013) examined whether children with ADHD showed deficits in visuospatial working memory. The basic procedure of the task was the same as the procedure mentioned above for Tsujimoto et al (2004).…”
Section: Ef In Children With Attention-deficit/hyperactivity Disordermentioning
confidence: 99%
“…Moreover, a significant correlation between error rates and right prefrontal activation was found in children with ADHD. Thus, hyperactivity in the right prefrontal regions may play a role in error-making during working memory tasks (Tsujimoto et al, 2013). …”
Section: Ef In Children With Attention-deficit/hyperactivity Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…The single group showed relatively flat prefrontal activation throughout the driving period regardless of players' game proficiency, suggesting that the driving‐game task used in the present study may not active the PFC due to the task easiness. (Tsujimoto et al., ; Wan et al., ). In contrast, the NIRS data of the paired group showed decreased prefrontal activation in low‐proficiency players and increased prefrontal activation in high‐proficiency players.…”
Section: Discussionmentioning
confidence: 99%